OC-005 Novel Pathway-centric Analysis Reveals Variants Associated With Toxicity And Response To Thiopurines In Patients With Inflammatory Bowel Disease. (9th June 2014) - Blaker, PA; Fong, S; Walker, J; Lewis, CM; Marinaki, AM; Sanderson, JD; Irving, PM
Abstract : Introduction: Thiopurines remain the first line immunosuppressants recommended in the management of inflammatory bowel disease (IBD). Unfortunately, 30–40% of patients prescribed these agents develop adverse drug reactions or fail to derive therapeutic benefit. Candidate gene studies have identified loci that explain some of these treatment failures; however a substantial fraction of the genetic contribution remains undefined. Using whole thiopurine pathway analysis the aim of this study was to identify novel loci associated with toxicity and response to azathioprine (AZA)/mercaptopurine (MP) in patients with IBD. Methods: Genomic DNA was extracted from EDTA blood samples of 472 well-characterised IBD patients treated with AZA/MP. We examined exome array data using the Illumina HumanExome Beadchip and restricted the analysis to variants associated with the thiopurine pathway as defined by the KEGG database (100 genes, 639 single nucleotide polymorphisms). Using a case-control design we firstly tested for genetic associations between patients with ( n = 1 54) and without ( n = 2 58) adverse drug reactions, and secondly for polymorphisms differentiating patients with ( n = 1 88) and without ( n = 1 41) response to thiopurines after 12 months of treatment. One year intervention-free clinical response was defined by 3 investigators (PB, PI, JS). Results: Following adjustment for principal components, the minor alleles at ADK rs946185 (p = 0.0078; OR 1.675), SLC28A1 rs2242046 (p = 0.0168; OR 1.600) and ABCA1 rs4149268 (p = 0.033; OR 1.487) were associated with the development of drug toxicity, whereas the minor alleles at ABCB5 rs2301641 (p = 0.0170; OR 0.608), ABCC4 rs4148549 (p = 0.027; OR 0.652) and AOX1 rs55754655 (p = 0.038; OR 0.549) protected against it. The minor allele at RRM2 rs1130609 (p = 3.80 × 10 –5 ; OR 0.461), which codes a subunit of ribonucleotide reductase involved in the conversion of thioguanine nucleotide to deoxy-thioguanine nucleotide, and a higher normalised dose of AZA/MP were associated with protection from non-response. Conversely, the minor allele at ABCA1 rs2230808 (p = 0.008; OR 2.585) and Crohn's disease (p = <0.001; OR 5.007) were associated with non-response to treatment at 12 months. Conclusion: High-throughput sequencing using exome array technology has revealed new loci, other than thiopurine- S- methyltransferase, explaining toxicity and response to thiopurines. Validation of these markers in separate cohorts will allow the development of biomarker panels to predict outcomes prior to the start of treatment. Disclosure of Interest: None Declared.